A Survey on Operation Concept, Advancements, and Challenging Issues of Urban Air Traffic Management - Shrestha, Rakesh; Oh, Inseon; Kim, Shiho (Frontiers in Future Transportation, 2021)
The recent growth and adoption of Unmanned Aerial Vehicles (UAVs) is due to its low development cost, high aerial mobility, advanced battery technology, rotors, gyroscopes, GPS, cameras, sensors and a wide range of applications. The UAV offers new possibilities for business in civil and non-civil applications such as parcel delivery, aerial mapping, agriculture, wildlife conservation, surveillance, search and rescue, etc. However, considering the exponential growth in various types of aerial vehicles, it is clear that advanced air traffic management services are urgently needed to control and handle the ever increasing air traffics. In this paper, we first present the two major low altitude UAV traffic management system in the USA and Europe and compare them thoroughly. We present the global vision and advancement of UAV traffic management system, and then discuss the existing research trends. Understanding the complexity of future air transportation system, we discuss the necessary elements required for urban air traffic management system. We provide key strategic elements for an advanced urban traffic management through connectivity, open source, safety enhancement and automation to maximize its impacts on the innovative future air traffic and mobility system. In the end, we discuss the challenging security issues in urban traffic management system.